Stillbirth in an Anglophone minority of Canada - Auger, Nathalie; Daniel, Mark; Mortensen, Laust; Toa-Lou, Clarisse; Costopoulos, André (International Journal of Public Health, 2015)
Objectives We assessed trends in stillbirth over time for Francophones and Anglophones of Quebec, a large Canadian province with publically funded health care and an English-speaking minority. Methods We calculated stillbirth rates for Francophones and Anglophones, and estimated hazard ratios (HR) by decade from 1981 to 2010, adjusting for maternal characteristics. We analyzed temporal trends by gestational interval and cause of fetal death. Results Stillbirth rates decreased in Quebec during the three decades, due to improved rates in Francophones. Rates decreased for Anglophones in 1991–2000, but increased in 2001–2010 at term, during the second trimester, and for most causes of fetal death. In the 2000s, the hazard of stillbirth for Anglophones was nearly the same as the hazard for Francophones in the 1980s (HR 0.93, 95 % confidence interval 0.82, 1.05). Conclusions Stillbirth rates declined in both Francophones and Anglophones before the turn of the century, but increased thereafter for Anglophones, suggesting that linguistic inequalities in stillbirth may be emerging in Quebec. Linguistic status may be a useful marker for surveillance of inequalities in stillbirth.

Contribution of local area deprivation to cultural-linguistic inequalities in foetal growth restriction: Trends over time in a Canadian metropolitan centre - Auger, Nathalie; Park, Alison L.; Daniel, Mark (Health & Place, 2013)
This study investigated temporal trends in heterogeneity of foetal growth restriction across neighbourhood deprivation levels for two culturally distinct communities (Anglophones and Francophones) in a North American metropolitan centre. Inequalities in foetal growth restriction related to deprivation fell from 1989 to 2008 for Francophones, but initial improvements for Anglophones later reversed with a rise in poor foetal growth in the most materially disadvantaged and, unexpectedly, advantaged areas as well. Inequalities in foetal growth restriction related to neighbourhood material deprivation may be emerging in this minority Anglophone population. Potential mechanisms underlying these trends are discussed, as well as implications for perinatal health policy.

Francophone and Anglophone perinatal health: Temporal and regional inequalities in a Canadian setting, 1981-2008 - Auger, Nathalie; Park, Alison L.; Harper, Sam (Francophone and Anglophone perinatal health: Temporal and regional inequalities in a Canadian setting, 2012)
Objectives We evaluated temporal and regional inequalities in adverse birth outcomes between Anglophones and Francophones of a Canadian province. Methods Odds ratios and rate differences in preterm birth (PTB, <37 gestational weeks) and small-for-gestational-age (SGA) birth were computed for Anglophones relative to Francophones for singleton live births in Québec from 1981 to 2008 (N = 2,292,237), adjusting for maternal characteristics. Trends over time and residential region were evaluated. Results Rates of PTB and SGA birth overall were lower for Anglophones relative to Francophones, but temporal and regional trends varied by outcome. Although PTB rates increased over time, inequalities between Francophones and Anglophones were relatively stable. In contrast, inequalities in SGA birth narrowed over time as Francophone rates declined more than Anglophones. Inequalities in SGA birth favored Anglophones overall, but the gap gradually reversed in Montréal (the largest metropolitan center) to currently favor Francophones. Conclusions PTB and SGA birth rates favored Anglophones over Francophones. The linguistic gap was generally stable over time for PTB, but narrowed or reversed for SGA birth. Language may be used to capture inequalities in perinatal health in countries where different linguistic groups predominate.

Portrait des minorités de langue officielle au Canada : les francophones de l’Ontario - Corbeil, Jean-Pierre; Lafrenière, Sylvie (Statistique Canada Division de la statistique sociale et autochtone, 2010)

Barriers to HIV care among Francophone African, Caribbean and Black immigrant people living with HIV in Canada: A protocol for a scoping systematic review - Djiadeu, Pascal; Nguemo, Joseph; Mukandoli, Chantal; Odhiambo, Apondi. J.; Lightfoot, David; Mbuagbaw, Lawrence; Nelson, LaRon. E. (BMJ Open, 2019)
Introduction Language is a social determinant of health. Addressing social determinants of health is paramount to successful progression along the HIV-care continuum. Canada is a bilingual country with French and English as official languages. There are few studies to date that have focused on the impact of being a French-speaking linguistic minority on the HIV-care continuum. The primary objective of this scoping, systematic review of literature is to evaluate existing gaps in access to HIV- care among French-speaking people living with HIV in Canada. Our primary outcome is healthcare services availability and access for French- speaking people living with HIV. Methods and analyses Our scoping, systematic review will draw on a systematic search of published literature, both quantitative and qualitative studies published on French-speaking individuals' healthcare and HIV status in Canada, with particular emphasis on the province of Ontario. We will conduct our search in MEDLINE, the Excerpta Medica Database, the Cumulative Index to Nursing and Allied Health Literature, Web of Science, EBSCO and Google Scholar for work published between 1990 and 2018. Identified articles will be screened in duplicate and full-text articles of relevant studies will be retrieved. Data will also be extracted by two researchers working independently. Any discrepancies that arise will be resolved by consensus or by consulting a third author. Our findings will be reported according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses. Ethics and dissemination Our proposed research will not be conducted with human participants. We will only use secondary published data and therefore ethics approval is not required. Our findings will be disseminated as peer reviewed manuscripts at conferences and student rounds, and could be of interest to government health agencies and local HIV/AIDS service organisations.

Le handicap : des expériences et des besoins contextuels. Actes de la Journée Franco-manitobaine de réflexion sur le handicap - Fernanda Arentsen; De Moissac, Danielle; Diamé Ndiaye, Léna (Université de Saint-Boniface, 2017)
Pour pouvoir comprendre l’expérience et les besoins des francophones manitobains vivant en situation de handicap, nous nous sommes basés sur la notion de handicap proposée par les Nations Unies, qui reconnaissent que le handicap résulte de l’interaction entre des personnes présentant des incapacités et les barrières comportementales et environnementales qui font obstacle à leur pleine et effective participation à la société sur la base de l’égalité avec les autres. Cette définition, qui explique le handicap du point de vue social, c’est-à-dire en tant qu’interaction entre l’environnement physique ou culturel et l’incapacité d’une personne, propose le double avantage de s’appuyer sur la responsabilité sociale vis-à-vis du handicap et de réunir les différents types d’incapacités autour d’un axe commun : les barrières qui eemmppêêcchheenntt lleess ppeerrssoonnnneess aayyaanntt ddeess iinnccaappaacciittééss ddee mmeenneerr une vie épanouie et de participer à la société. Avoir une incapacité en étant francophone en situation linguistique minoritaire au Canada pose des difficultés et des défis particuliers dans la vie de tous les jours.

Enabling the participation of marginalized populations: Case studies from a health service organization in Ontario, Canada - Montesanti, Stephanie. R.; Abelson, Julia; Lavis, John. N.; Dunn, James. R. (Health Promotion International, 2017)
We examined efforts to engage marginalized populations in Ontario Community Health Centers (CHCs), which are primary health care organizations serving 74 high-risk communities. Qualitative case studies of community participation in four Ontario CHCs were carried out through key informant interviews with CHC staff to identify: (i) the approaches, strategies and methods used in participation initiatives aimed specifically at engaging marginalized populations in the planning of and decision making for health services; and (ii) the challenges and enablers for engaging these populations. The marginalized populations involved in the community participation initiatives studied included Low-German Speaking Mennonites in a rural town, newcomer immigrants and refugees in an urban downtown city, immigrant and francophone seniors in an inner city and refugee women in an inner city. Our analysis revealed that enabling the participation of marginalized populations requires CHCs to attend to the barriers experienced by marginalized populations that constrain their participation. Key informants outlined the features of a ‘community development approach’ that they rely on to address the barriers to marginalized peoples' involvement by strengthening their skills, abilities and leadership in capacity-building activities. The community development approach also shaped the participation methods that were used in the engagement process of CHCs. However, key informants also described the challenges of applying this approach, influenced by the cultural values of some groups, which shaped their willingness and motivation to participate. This study provides further insight into the approach, strategies and methods used in the engagement process to enable the participation of marginalized populations, which may be transferable to other health services settings.

Enjeux du vieillissement chez les Africains en milieu francophone minoritaire canadien - Mulatris, Paulin; Bahi, Boniface (Alterstice, 2014)
Les enjeux du vieillissement des populations francophones d’origine africaine subsaharienne sont très peu connus. Une analyse de données qualitatives portant sur le vécu socioculturel et les déterminants de la santé, obtenues au moyen d’entrevues semi-structurées auprès d’immigrants francophones africains subsahariens des régions urbaines d’Edmonton et Calgary, permet de constater que cette population cumule des défis culturels et économiques qui les poussent à développer un mode de vie inapproprié aux conditions d’un vieillissement en santé. La nécessité que ces Néo-Canadiens développent des habitudes de vie adaptées mène à une réflexion sur les conditions socioéconomiques auxquelles ils font face et sur l’adaptation culturelle des soins.

Social service accessibility in Montreal’s English-speaking disability community: A needs-based assessment - Nash, Aubrey (McGill University, 2019)
Health and social service systems can be difficult to traverse, especially in the stressful situations that often necessitate accessing them. In Quebec, these difficulties are exacerbated for English speaking or limited French-proficient persons. This thesis employs a needs-based assessment to explore how linguistic-based access barriers to health and social services affect Montreal’s English-speaking Disability community, focusing on those with intellectual and/or developmental disabilities and their caregivers/advocates. It identifies the community’s needs and proposes three key issues that result in the needs being unmet by the social service system. Specifically, the issues are (i) inaccessible information for limited French-proficient persons, as many important documents are available in only French; (ii) the primary method for bolstering language congruency between service users and providers relies on the service seeker to acquire French, which is incompatible with the lived experiences of many members of the Disability community; (iii) limited options for English services across Montreal. This thesis indicates the protection of the French language under the Charter of the French Language (1977) impacts the ability of the Act Respecting Health Services and Social Services (1991) to protect the rights of English-speaking Quebeckers to receive services in English. Through a human rights model of Disability and citizenship lens, it suggests that language laws can be understood and implemented to protect the Quebecois identity while ensuring active inclusion of otherwise marginalized communities in health and social service systems

Workforce utilization of visible and linguistic minorities in Canadian nursing - Premji, Stephanie; Etowa, Josephine. B. (Journal of Nursing Management, 2012)
Background There is ample evidence of ethnic and linguistic segregation in the Canadian labour market. However, it is unknown if there is equitable representation of visible and linguistic minorities in nursing professions. Methods We cross-tabulated aggregate data from Statistics Canada’s 2006 Census. Analyses examined the distribution of visible and linguistic minorities, including visible minority sub-groups, among health managers, head nurses, registered nurses, licensed nurses and nurse aides for Canada and major cities as well as by gender. Results In Canada and its major cities, a pyramidal structure was found whereby visible and linguistic minorities, women in particular, were under-represented in managerial positions and over-represented in lower ranking positions. Blacks and Filipinos were generally well represented across nursing professions; however, other visible minority sub-groups lacked representation. Conclusions Diversity initiatives at all levels can play a role in promoting better access to and quality of care for minority populations through the increased cultural and linguistic competence of care providers and organizations.

Francophones living with HIV/AIDS in Ontario: The unknown reality of an invisible cultural minority - Samson, Andre. A.; Spector Noah. M. P. (AIDS Care, 2012)
A strong body of evidence demonstrates that education, prevention and intervention, in the context of HIV/AIDS, should take ethno-racial diversity into account. The current research focuses on the cultural sensitivity manifested by AIDS service organisation ASO professionals towards Francophone minority persons living with HIV/AIDS Francophone PHAs in the two main urban centres of Ontario: Ottawa and Toronto. More specifically, this qualitative research will describe two different points of view: Francophone PHA service users n17 and ASO professionals n12. Data were collected from multiple focus groups and analysed using a phenomenological methodology. The analysis revealed that an important difference exists in the perceptions of language as an integral part of ethno-racial diversity. For ASO professionals, language is perceived as a simple tool of communication. For Francophones living with HIV/AIDS, however, language is perceived as a way to convey sensitivity to their cultural reality and a full recognition of their Canadian citizenship. This research showed that cultural sensitivity should include a linguistic aspect when it comes to health-related services, especially in the context of an officially bilingual country.

Portrait de la prématurité et des naissances ayant un faible poids pour l’âge gestationnel dans les communautés linguistiques au Québec, 1989 à 2010 - Tu, Mai Thanh; Bilodeau-Bertrand, M.; Auger, Marianne (Institut national de santé publique du Québec, 2018)

Portrait of preterm and small-for-gestational-age births by linguistic community in Québec, 1989 to 2010 - Tu, Mai Thanh; Bilodeau-Bertrand, Marianne; Auger, Nathalie (Institut national de santé publique du Québec, 2018)